Influence of Autoclave Sterilization of Human Teeth on Dentin Bonding - Paula JACQUES; Josimeri HEBLING (Association of Support to Oral Health Research (APESB), 2006)
Objective: The aim of this study was evaluate the effect of sterilization of human teeth used in laboratorial studies on dentin bonding. Method: Twenty extracted human third molars are distributed in two groups, with or without sterilization, GA and GB, respectively. The GA group was sterilized with steam autoclave at 120°C at 1Kgf/cm2 for 20min and both groups are sectioned using diamond disk to expose a flat oclusal dentin. The smear layer was standardized with carbide bur and one off adhesive systems was applied, Adper Singe Bond or Clearfil SE Bond before fill with resin composite. The specimens - sticks are stored in water at 37°C for 24h, before fixation of him in a device and then tested in a mechanical testing machine until occur at failure. Results: The mean of microtensile bond strength are, to GA group, 59.81MPa for SB, 53.08 for CSE, while for GB group, 49.65 for SB and 50.56 for CSE. Conclusion: The sterilization influenced positively, with increasing of bond strength to SB system and no influenced significantly on CSE system.